Transnational Chinese Diaspora in Southeast Asia Case Studies from Thailand, Malaysia, and Singapore - Santasombat, Yos (Springer Nature Singapore : Imprint: Springer, 2022)
XII, 164 p. 9 illus., 5 illus. in color.